Pengaruh Konsentrasi Asam Sulfat (H2SO4) pada Hidrolisa Tongkol Jagung (Zea mays) Menjadi Nanokristal Selulosa sebagai Filler Penguat pada Produk Lateks Karet Alam - Harahap, Hamidah; Harfansah Nst, Azwin; Fujian Junaidi, Ilhamdi (Jurnal Teknik Kimia USU, 2019)
This research studied about the effect of concentrations sulfuric acid (H2SO4) on the hydrolysis process of corn cobs waste to manufacture of cellulose nanocrystal (NCC) which will be applied as fillers in natural rubber latex. This study began with a pre-vulcanization process of natural rubber latex at a temperature of 70 oC and followed by a vulcanization process at 110 oC for 10 minutes. The results of the testing of physical properties indicate that the higher amount of NCC loading will result in higher crosslinked denotes, while the results of testing the mechanical properties indicate that the maximum value is achieved at the loading of NCCs as much as 6 phr. The mechanical test results supported by the analysis of Scanning Electron Microscopy (SEM) showing the NCC have spread well. Characterization of the Transform Electron Microscope (TEM) shown the resulting of NCC was spherical shape with the size of NCC produced for each concentration of sulfuric acid (H2SO4) 45%, 55%, and 65% respectively 57.65 nm; 28.43 nm; and 82.61 nm with an amount of each 0.849 g; 1,824 g; and 0.681 g. The mechanical and physical properties of the optimum natural rubber latex products occurred in the loading of nanocrystal cellulose with a number of 6 bsk, where the values ​​of cross-connect density, tensile strength, elongation at break, M200 and M300 were respectively 10.6234 2Mc-1x10- 5; 18.2 MPa; 780%; 2.23 MPa and 2.7 MPa.